2018
DOI: 10.1186/s12886-018-0775-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of Transepithelial photorefractive keratectomy to treat low to moderate myopic astigmatism

Abstract: BackgroundTo evaluate the refractive and visual outcomes of Transepithelial photorefractive keratectomy (TransPRK) in the treatment of low to moderate myopic astigmatism.MethodsThis retrospective study enrolled a total of 47 eyes that had undergone Transepithelial photorefractive keratectomy. Preoperative cylinder diopters ranged from − 0.75D to − 2.25D (mean − 1.11 ± 0.40D), and the sphere was between − 1.50D to − 5.75D. Visual outcomes and vector analysis of astigmatism that included error ratio (ER), correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…Safety, efficacy, and predictability of TransPRK have been proved by several previous studies [12][13][14][15][16]. e application of smart pulse technology (SPT) in all surface laser ablation (ASLA) causes better early postoperative visual recovery and faster epithelial healing [6].…”
Section: Discussionmentioning
confidence: 99%
“…Safety, efficacy, and predictability of TransPRK have been proved by several previous studies [12][13][14][15][16]. e application of smart pulse technology (SPT) in all surface laser ablation (ASLA) causes better early postoperative visual recovery and faster epithelial healing [6].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that TPRK, PRK or LASEK are efficient and safe methods to correct low and moderate myopia [10,11]. However, for high myopia, the stability and predictability of correction may be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have compared the efficacy of different surgical techniques in correcting myopic astigmatism [20][21][22][23][24][25]. A consistent finding of these reports is that visual and refractive outcomes are better in eyes with lower, rather than higher cylindrical error.…”
Section: Discussionmentioning
confidence: 93%